2014
DOI: 10.1007/s11356-014-2580-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of di-n-butyl phthalate on the physiology and ultrastructure of cucumber seedling roots

Abstract: Agricultural pollution caused by the use of plastic sheetings has been documented to be a widespread problem in most of the major crop-planting regions of the world. In order to better understand the phytotoxic mechanisms induced by phthalic acid esters involved with this problem, Cucumber sativus L. cv Jinyan No. 4 were sown in pots to the three-leaf-stage in the presence of di-n-butyl phthalate (DBP; 0, 30, 50, 100, and 200 mg L−1) for 1, 3, 5, or 7 days. Physiology, biochemistry, and ultrastructure of seedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…The increased contents of MDA and Pro and the decreased content of POD in this study indicated the damage of membrane system. The changes in the MDA and Pro contents were approximately the same as those observed by Zhang et al (2014). But changes in the POD content did not have the same trend to other studies.…”
Section: Discussionsupporting
confidence: 69%
“…The increased contents of MDA and Pro and the decreased content of POD in this study indicated the damage of membrane system. The changes in the MDA and Pro contents were approximately the same as those observed by Zhang et al (2014). But changes in the POD content did not have the same trend to other studies.…”
Section: Discussionsupporting
confidence: 69%
“…The adverse effects of PAEs on microorganism communities were not surprising, as di-(2-ethylhexyl) phthalate and diethyl phthalate have been reported to change microorganism communities in soils [35,36]. DBP can affect plant root membrane permeability [37]; thus, it is possible that DBP toxicity might lead to the root leakage of organic compounds that can affect soil microbial communities.…”
Section: Discussionmentioning
confidence: 99%
“…However, particle precipitation after volatilization from and direct release of PAEs from plastic film are supposed to be the main sources in soils in polytunnel greenhouses (Wang et al 2007). PAE contamination in vegetables such as rape in Nanjing and toxicity effects on the physiology and ultrastructure of cucumber seedling roots have been recorded (Cai et al 2008;Chai et al 2008;Zhang et al 2014); however, contamination of soils and vegetables in poly-tunnel greenhouse has not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%